Development of a knowledge economy model based on the application of digital technologies in the republic of Kazakhstan - Nurgalieva, A.; Tovma, N.A.; Bianchi, I. (BUKETOV BUSINESS REVIEW, 2023)
Object: the purpose of the study is to develop a model of the knowledge economy based on the use of digital technologies in the Republic of Kazakhstan. Research methods — questioning, survey, extrapolation, comparison. Methods: the study was carried out in three stages. At the initial stage, primary data were collected, 6 questionnaires were developed, 147 people were interviewed. Findings: the purpose of the study is to develop a model of the knowledge economy based on the use of digital technologies in the Republic of Kazakhstan. Research methods — questioning, survey, extrapolation, comparison. The main results of the study: the existing models of the development of the knowledge economy were studied, the main indicators of the knowledge economy in Kazakhstan and abroad were considered, it was revealed due to which measures taken foreign countries are leading in terms of knowledge economy indicators, forecast calculations of the main indicators of the knowledge economy were given, a model for the development of the knowledge economy was developed using digital technologies, which will increase the country's competitiveness and move to a new level of development and will contribute to the entry of the Republic of Kazakhstan into the top 30 most developed countries in the world. Conclusions: without knowledge, the development of a post-industrial society is impossible. In this regard, a new knowledge-based economy stands out. The developed countries of the world have moved to a new development model — to the knowledge economy. To increase the competitiveness of the Republic of Kazakhstan, it is also necessary to move to a new stage of development — the knowledge economy. According to a number of indicators, the Republic of Kazakhstan lags behind other countries.